2022
DOI: 10.1177/10760296221100806
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Monocyte Count and Preoperative Deep Venous Thrombosis in Older Patients with hip Fracture: A Retrospective Study

Abstract: Purpose To analyze the relationship between monocyte count and preoperative deep venous thrombosis (DVT) in older patients with hip fracture. Methods Consecutive older patients with hip fracture undergoing surgery were included from January 2014 to December 2021. Monocyte count was measured on admission, and Doppler ultrasonography was performed for DVT screening prior to surgery. Univariate and multivariate logistic regression analyses were used to assess the association between monocyte count and DVT. Result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…In a recent retrospective study of 674 older patients with hip fracture Wang et al found that a monocyte count above 0.6 × 10E9/L in a multivariate analysis was independently associated with a preoperative risk of DVT (OR 1.705 × 95%CI 1.12–2.59), but not for PE [ 22 ]. A register study with Mendelian Randomization on a genome-wide association study He et al found that a genetically predicted monocyte count was negatively correlated with VTE, but does not discriminate between DVT and PE, and has no information about time of VTE examination blood sample drawn [ 23 ], and level of monocyte count.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent retrospective study of 674 older patients with hip fracture Wang et al found that a monocyte count above 0.6 × 10E9/L in a multivariate analysis was independently associated with a preoperative risk of DVT (OR 1.705 × 95%CI 1.12–2.59), but not for PE [ 22 ]. A register study with Mendelian Randomization on a genome-wide association study He et al found that a genetically predicted monocyte count was negatively correlated with VTE, but does not discriminate between DVT and PE, and has no information about time of VTE examination blood sample drawn [ 23 ], and level of monocyte count.…”
Section: Discussionmentioning
confidence: 99%
“…As described above, these blood indicators were significant predictors of death after hip fracture ( 10 , 13 15 ). Furthermore, we also found that high monocyte level was associated with an increased risk of deep venous thrombosis (DVT) in older patients with hip fracture, thereby leading to a 3.21-fold increase in the 30-day mortality ( 29 , 30 ). From these findings, we hypothesized that high SIRI level would be an independent predictor of subsequent death following hip fracture.…”
Section: Introductionmentioning
confidence: 85%
“…Monocytes/macrophages also participate in removing apoptotic cells and tissue debris, contributing to the resolution of inflammation. Due to the diverse functions that monocytes or macrophages perform during the development of inflammation and regulation of the coagulation cascade and tissue regeneration, dysregulation of their functions may affect coagulation disorders and thrombotic diseases such as Deep Vein Thrombosis (DVT) [ 74 , 89 , 90 ] and Pulmonary Embolism (PE) [ 90 , 91 ], Arterial Thrombosis [ 92 , 93 ], Disseminated Intravascular Coagulation (DIC) [ 94 ], Antiphospholipid Syndrome (APS) [ 95 , 96 ], or Thrombotic Microangiopathies [ 97 , 98 ], highlighting the importance of understanding their interaction with the coagulation system ( Table 2 ).…”
Section: Blood Coagulation Process and The Role Of Immune System Cellsmentioning
confidence: 99%